Current Concepts in Knee Dislocations: PCL, ACL, and Medial Sided Injuries - Stannard, James P.; Bauer, Kathryn L. (The Journal of Knee Surgery, 2012)
Dislocations resulting in multiligament knee injuries are challenging to treat and diagnose. With proper diagnosis and anatomic reconstruction techniques, patients can have successful outcomes. This article describes the senior author's (J.P.S.'s) preferred reconstruction techniques, timing for surgery, and rehabilitation techniques for injuries involving the anterior cruciate ligament (ACL), posterior cruciate ligament (PCL), and posteromedial corner (PMC). We prefer to address these injuries in a staged fashion. The PCL, PMC, and any additional meniscal pathology are addressed in the index procedure. The ACL is reconstructed approximately 6 weeks later to ensure that acceptable range of motion has been regained. Staging procedures also allow time to maximize rehabilitation protocols for both the PCL and the ACL.
Keywords: knee dislocation; anterior cruciate ligament; posterior cruciate ligament; posteromedial corner; multiligament